2003
DOI: 10.1017/s1041610203009517
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Geriatric Depression Scale for Use Among Elderly Asian Immigrants in the USA

Abstract: The increasing numbers of Asian and other immigrants in the United States have resulted in greater demands for research methodology sensitive to crosscultural issues. A regional probability sample (n = 407) of Asian elderly immigrants of different nationalities (Chinese, Korean, Indian, Filipino, Vietnamese, or Japanese) residing in New York City was used to examine the reliability of the Geriatric Depression Scale (GDS). Using the 30-item GDS, about 40% of this representative sample of Asian elderly immigrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 21 publications
0
42
0
1
Order By: Relevance
“…This instrument has been widely used and is highly regarded as a culturally sensitive measure of this complex mental health outcome [36][37][38]. Each item was coded as 0 = have no symptoms and 1 = have symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…This instrument has been widely used and is highly regarded as a culturally sensitive measure of this complex mental health outcome [36][37][38]. Each item was coded as 0 = have no symptoms and 1 = have symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Depression was measured by a 15-item Geriatric Depression Scale (GDS), which was translated, adapted, and validated to better fit the cultural context of the Asian elderly in North America (Mui et al 2003). Scores were assigned to participants who indicated positive answers to items that represent depression.…”
Section: Methodsmentioning
confidence: 99%
“…In previous cross-cultural studies of Asian American elderly immigrants, high prevalence rates of depression were reported, compared to their nonAsian or native-born peers (Lam, Pacala, & Smith, 1997;Mui, Kang, Chen, & Domanski, 2003). In these studies, life satisfaction, social support, health Downloaded by [Lakehead University] at 13:30 08 December 2014 status, functional status, number of years present in the United States, level of acculturation, and command of the English language were all found to be inversely related to depressive symptoms.…”
Section: Asian American Mental Health and Resiliencymentioning
confidence: 99%